LEGAL IMPLICATIONS OF REGULATING ARTICLES 38 AND 39 OF LAW NUMBER 1 OF 2023 (CRIMINAL CODE) ON CRIMINAL LIABILITY FOR PERSONS WITH DISABILITIES - Canthika Mira Istiyanthi; Faizin Sulistio; Abdul Madjid (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research analyzes the juridical implications of Articles 38 and 39 of Law Number 1 of 2023 (Criminal Code) on the construction of criminal liability for persons with disabilities in Indonesia's criminal justice system. Through a juridical-normative approach, the research identifies a paradigmatic transformation from a paternalistic model toward a rights-based approach, albeit with implementation challenges encompassing conceptual ambiguities, procedural limitations, and structural barriers. The findings demonstrate the urgency of reorienting criminal liability construction through developing a "Differential Criminal Responsibility" model that integrates principles of proportionality, individualization, and adaptive support aligned with international standards. Recommendations include legislative harmonization, assessment protocol development, institutional capacity enhancement, and diversification of rehabilitation-based legal consequences to optimize legal protection for persons with disabilities within an inclusive and equitable criminal justice system. Keywords: Criminal Liability, Persons with Disabilities, Criminal Code 2023